2009
DOI: 10.1007/s10592-009-9932-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite loci for the jack mackerel (Trachurus murphyi Nichols, 1920)

Abstract: Eight microsatellite loci were developed for the jack mackerel (Trachurus murphyi), a fish of significant commercial importance in the Southeast Pacific. Genetic variation at these loci was examined in 15 samples from the locality of Talcahuano (Chile). All eight were highly polymorphic, with a number of alleles per locus ranging from 4 to 22 and an observed heterozygosity from 0.429 to 1. These markers will be useful to address issues of population genetics, ecology, conservation and fisheries management rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Individuals were analysed at 10 microsatellite loci, four of which (Tt29, Tt48, Tt62, Tt113) were developed for T. trachurus (Kasapidis & Magoulas, ) and six (TmurA101, TmurA104, TmurA115, TmurB104, TmurB116, TmurC4) for T. murphyi (Canales‐Aguirre et al ., ). Loci were individually PCR amplified in 10 μl reaction volumes containing 50–100 ng template DNA, 1 pmol of each primer, 5 μl of 2XBioMix (Bioline, UK) and 1 μl of ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals were analysed at 10 microsatellite loci, four of which (Tt29, Tt48, Tt62, Tt113) were developed for T. trachurus (Kasapidis & Magoulas, ) and six (TmurA101, TmurA104, TmurA115, TmurB104, TmurB116, TmurC4) for T. murphyi (Canales‐Aguirre et al ., ). Loci were individually PCR amplified in 10 μl reaction volumes containing 50–100 ng template DNA, 1 pmol of each primer, 5 μl of 2XBioMix (Bioline, UK) and 1 μl of ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…The Wahlund effect has been suggested as a cause for heterozygous deficiency, (Johnson and Black, 1984;Pritchard et al 2000;Valles-Jimenez et al 2005;Zelenina & Rastorguev, 2010;Buryakova & Glubokov, 2011;Bekkevold et al 2011;Afanaziev, et al 2012 andOvenden, 2013). The results shows the presence of null alleles as indicated by the low F is values (homozygous deficit) and this is a common problem in population studies using microsatellites, (Hauser et al 2002;Ball and Chapman 1998;Burridge and Smolenski, 2003;Cristian et al 2009;Tzeng et al 2009;Bekkevold et al 2011;.Nugroho et al 2011). Assortative mating and reproductive success (Supungul et al 2000) could lead to inbreeding and HW disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Two microsatellite loci, TmurA115 TG (28) Genbank (FJ668658) F: GTCACTGGAGCAATCAATAGAC R: TGCAATGTTACATGACTCAGAG and TmurB104 F: TGAAGCACAAGTTTCCAAATC ATC (14) Genbnk (FJ668661) R: AAAGGTCAGAGAGAGAACAACG developed by Cristian et al (2009) were used in this study. Mendelian inheritance mode of these loci in all families was studied.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…The average values of Na , Ho , He , and PIC of these 33 loci were 12.6, 0.723, 0.827, and 0.794, respectively. These genetic parameters were nearly equivalent to those previously reported for 11 di‐nucleotide repeat SSRs ( Ho = 0.70, He = 0.81) (Chang et al., 2009) and 37 di‐ and tri‐nucleotide repeat SSRs ( Na = 13.73, Ho = 0.739, He = 0.807, PIC = 0.771) in T. japonicus (Liang et al., 2019) and were higher than those for eight di‐nucleotide repeat SSRs in Trachurus murphyi ( Na = 10.88, Ho = 0.709, He = 0.786) (Canales‐Aguirre et al, 2010) and 28 di‐ and tri‐nucleotide repeat SSRs in Lepturacanthus savala ( Na = 9.11, Ho = 0.634, PIC = 0.670) (Zhang et al., 2018). Our results showed that the developed polynucleotide‐repeat SSRs in the present study exhibited moderate to relatively high genetic diversity in T. japonicus .…”
Section: Discussionmentioning
confidence: 99%